Protection Of Civil Rights In Cases Of Grave Human Rights Violations During The Sudan Conflict Through The International Criminal Court - Inayatuzzahra, Inayatuzzahra (Fakultas Hukum Dehasen, 2025)
International criminal law and international humanitarian law have long sought to protect civilians in armed conflict. The International Criminal Court (ICC) seeks to prosecute perpetrators of serious crimes in Sudan such as genocide, war crimes and crimes against humanity. The ICC seeks to investigate and prosecute perpetrators of crimes with the aim of providing justice for victims and strengthening human rights norms in the Sudan Conflict. This research discusses the protection of the rights of civilians who suffered severe human rights violations in the Sudan conflict through the international criminal court (ICC) with reference to the 1998 Rome Statute. This research uses normative legal research methods in the form of literature studies or document studies on written regulations or other legal materials.